THE DEVELOPMENT OF THE CONCEPT OF MATTER IN THE PHYSICAL VISION OF THE WORLD - Efendiyev, F.M; Dashdamirova, C.F (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The issue of matter is extremely actual in philosophy and natural sciences. It can be explained by complexity of the periodicity of elementary particles as well as by difficutty of experimental arqumentation of various hypotheses about the existence of quantum and tachyon (tahchyon is a hypothetical particle that always moves taste - than light: quantum - is the minimum amount of any phisical entity involved in an interaction). There must be two mayor principles with regard of this problematics: A) The argumentation of matter as philosophical category; B) The assumption concerning the infinity of categories and material attributes. Matter is inbinite in all organithation levels of it. It is on abstract concept, become just the types of matter really exist. Substance is determined by volume and vacuum ( the reality of virtual particles). There are some common elements in all historical views regarding material reality - the material unity of the world proves the assumption about various forms of material reality.